Multi-omics profiling unravel the immune landscape diversity by prognostic signatures of immunotherapy response in triple-negative breast cancer - Chai, Rong; Zhang, Ziting; Gong, Zheng; Li, Qi; Dong, Chunyan (Frontiers in Immunology, 2025)
BackgroundTriple-negative breast cancer (TNBC) remains a challenging malignancy with limited therapeutic options and variable responses to immune checkpoint inhibitors (ICIs). The tumor immune infiltration significantly influences the outcomes of immunotherapy treatments. Novel biomarkers are urgently needed which integrate both tumor-intrinsic and immune-related features to better stratify patients and dissect the immune microenvironment.MethodsWe investigated the tumor immune infiltration and assessed its prognostic significance in an internal cohort of TNBC patients using multiplex immunofluorescence. Then we integrated multi-omics approach that combines bulk and single-cell RNA sequencing to develop a prognostic signature. The model underwent validation across three independent external cohorts and additional immunotherapy cohorts. Immune cell infiltration was assessed using CIBERSORT, and cellular communication networks were characterized through CellChat analysis. Expression and functional investigations of key genes were conducted in TNBC cell lines using knockdown and overexpression techniques and further functional assays.ResultsOur internal cohort of patients with TNBC revealed distinct TIME profiles and both high CD8+ T cell density (HR = 0.22, 95%CI: 0.05-0.92, P = 0.0164) and low Treg density (HR = 5.836, 95%CI: 1.60-21.37, P = 0.0004) were independently associated with improved overall survival. Integrated characterization of tumor and immune features, a four-gene prognostic signature comprising CD276, MS4A1, IGFBP1, and CD200 was established. The signature categorized TNBC patients into distinct risk strata exhibiting varied survival outcomes and distinguished tumor immune infiltration conditions. The low-risk group exhibited enhanced immune infiltration, effector T cell activity, and favorable responses to ICIs therapy. Conversely, the high-risk group showed an immunosuppressive microenvironment. Immunofluorescence revealed a spatial association and potential functional interplay between MS4A1, CD200 and CD8+ T cells. In vitro researches demonstrated that CD276 enhances cell growth and migration, whereas IGFBP1 exerts protective effects.ConclusionsWe developed and validated an immune-related signature for predicting TNBC outcomes and immunotherapy response. This signature reflects underlying immune landscape heterogeneity and provides a crucial method for patient stratification and immunotherapeutic planning.